Knowledge, Attitude and Practice of Dental Students, Interns and Practitioners Towards the Phase-Down of Dental Amalgam in A Dental Institution of Libya - Salama Shaban; Seham Elsawaay; Sirageddin Alhmadi; Ahmed Mhanni (AlQalam Journal of Medical and Applied Sciences, 2024)
Amalgam has historically been a widely used restorative material for posterior teeth, valued for its longevity. However, concerns about mercury-related health risks and aesthetic drawbacks have led to a decline in its usage. This study aimed to assess the knowledge, attitudes, and practices of dental students, interns, and practicing dentists regarding dental amalgam in dental institutions in western Libya. A cross-sectional survey was conducted with 409 participants, including dental students, interns, dental officers, and faculty members. The questionnaire consisted of 18 questions related to the knowledge, utilization, and safety of dental amalgam. Data analysis using SPSS version 27 revealed that most participants rarely used amalgam, influenced by aesthetic concerns and patient preferences. There was a clear preference for composite resin as an alternative restorative material, indicating a trend towards discontinuing amalgam due to safety and environmental issues. The study concluded that most respondents rarely use dental amalgam, primarily due to aesthetic considerations, patient preferences for tooth-colored materials, and increased awareness of mercury toxicity. كان الأملغم مادة ترميمية شائعة لسنوات طويلة للأسنان الخلفية بسبب طول عمرها. ومع ذلك، أدت المخاوف بشأن المخاطر الصحية المرتبطة بالزئبق والقيود الجمالية إلى تقليل استخدامها. هدف هذه الدراسة إلى تقييم المعرفة والمواقف والممارسات لدى طلاب الأسنان والمتدربين وأطباء الأسنان الممارسين فيما يتعلق بمادة الأملغم في المؤسسات التعليمية لطب الأسنان في غرب ليبيا. تم إجراء مسح مقطعي شمل 409 مشارك، بما في ذلك طلاب الأسنان والمتدربين وأطباء الأسنان وأعضاء هيئة التدريس. تضمن الاستبيان 18 سؤالًا يتعلق بالمعرفة والاستخدام والسلامة لمادة الأملغم. أظهرت تحليل البيانات باستخدام النسخة 27 من برنامج SPSS أن معظم المشاركين استخدموا الأملغم بشكل نادر، متأثرين بالمخاوف الجمالية وتفضيلات المرضى. كان هناك تفضيل واضح لمادة الكمبوسيت كمادة ترميمية بديلة، مما يشير إلى اتجاه نحو التوقف عن استخدام الأملغم بسبب القضايا المتعلقة بالسلامة والبيئة. خلصت الدراسة إلى أن المشاركين نادراً ما يستخدمون الأملغم، ويرجع ذلك أساسًا إلى الاعتبارات الجمالية وتفضيلات المرضى للمواد ذات اللون المشابه للأسنان، وزيادة الوعي بالتسمم الزئبقي وقضايا السلامة